Pengembangan Portal Pendidikan Taman Kanak-Kanak Aisyiyah - Sanyoto, Bangkit; , Azizah Fatmawati, S.T., M.Cs (2017)
The importance of early childhood education makes Pimpinan Daerah Aisyiyah (PDA) Dikdasmen Council further enhance thr provision of information about profesional educational institutuons, informative and realible. Meeting the needs of such information services developed portal aplications Kindergarten Education Aisyiyah. Through the development of such systems can provide information Kindergarten Aisyiyah of several branches and twigs Aisyiyah. There are currenttly still using the data search proses that led to bookkeeping requires a lot of time. The development of the education portal is believed to facilitate the search data. The method used to develop applications include requirements analysis, system design, implementation, testing supplemented with a questionnaire to find out the results and benefits of the system that has been developed. Furthermore, in the development of this application which programming languange used is PHP programming languange, is supported by the use of CSS to refine the display interface, basisdata using MySQL, the use text editor Sublime Text. Based on test results using methods known to the system can blackbox valid while the questionnaire can be seen running well proven system of sample conducted 39 teachers from 6 TK 82.17% responded that the development of this system is easy to use and as needed.